"Running Trains" and "Sexing-In": The Functions of Sex Within Adolescent Gangs. Issue 2 (March 2019) - Quinn, Katherine; Dickson-Gomez, Julia; Broaddus, Michelle; Pacella, Maria
Gang members are exposed to unique sexual risks, yet little work has explored the influence of gang social norms. This study examines the functions and meanings of sex within gangs, with a specific focus on the ways in which sex is used to reinforce gang membership and norms, gender roles, and group cohesion. We conducted 58 semi-structured interviews with adolescent members of six gangs. Data were analyzed using thematic content analysis and constant comparative method in MAXQDA. Sexual risk behaviors within gangs are upheld and reinforced through unspoken norms and expectations. These high-risk sexual practices increase group cohesion and reinforce gender norms and power differences. Despite the prevalence of such practices, many gang members felt regret and remorse over their participation but noted it was just part of "the life." Our findings highlight the need for interventions to address the norms of the gang that reinforce sexual risk behavior.